Pengaruh Media Sosial Terhadap Citra Tubuh Pada Remaja Dan Dewasa Awal - Titin Sutini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: this literature study was compiled to determine the effect of the use of social media on individual perceptions regarding body image.Methods: This research is a rapid literature review. The literature search process uses the PICO approach in three data sources, namely Google Scholar, PubMed, and EbscoHost. Inclusion criteria included a population of adolescents and early adults, articles spanning the last five years, full articles, and in English or Indonesian. The articles obtained were then tested for feasibility using JBI Critical Appraisal Tools.Results: Based on the search results, 330 articles were obtained which then went through a selection process so that 4 articles were analyzed with a total sample of 1263 respondents aged 13-26 years who had body image disorders.Conclusion: Social media has more negative influence on a person's perception of his body, compared to positive influence